Selecting cement slurries for oil and gas production wells in deepwater areas - Hieu, Pham Quang (Petrovietnam Journal, 2013)
Drilling operations in deepwater areas such as the north and west of Norway, the west of Shetland, the Gulf of Mexico, the east of Venezuela and the west coast of South America face great potential risks and challenges with the sea water depth going up to thousands of metres. Furthermore, the cost of drilling wells in deepwater areas has increased significantly. It is, therefore, a pressing issue in deepwater well design to reduce the drilling time, optimise the well construction process and ensure well engineering. This article studies the choices of cement slurries, one of the important technological and technical solutions to improve the effectiveness of cementing wells in the deepwater areas.